De espíritu clásico, fálica o ambivalente: la fémina vargasllosiana de los años 80 - Tuesta Figueroa, Teresa Adelaida Aurora (2016)
Along with the publication of La Señorita de Tacna, Kathie y el hipopótamo and La Chunga, Mario Vargas Llosa’s first plays, the female characters of the author, who had been moved to a secondary role in their narrative are the protagonists of the action. Classical, phallic, or governed by its essence, the vargasllosian women reveals a critical portrait of the patriarchal estates in the author’s literatura.